Implications of Legal Regulations on the Protection of the Rights of Victims of the Dissemination of False Information (Hoaxes) Through Instagram Media - Galih Saputra; M. Yusran bin Darham; Faris Ali Sidqi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The results of the study show that the State in order to provide legal protection for the rights of victims of false information (hoax) through Instagram media in order to create order by enacting Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. In addition, every victim of crime has the right to be protected as regulated in Law Number 31 of 2014 concerning Amendments to Law Number 13 of 2006 concerning Protection of Witnesses and Victims, however, these two laws do not specifically regulate in providing protection for the rights of victims of false information through Instagram media. Law Number 31 of 2014 that those who are said to be victims are those who experience physical, mental, and/or economic loss caused by a crime. In cases of spreading false information or hoaxes, people who are considered victims must experience the direct consequences of the crime, whether in the form of physical, mental or economic financial losses. As for the protection of the rights of victims due to false information, they can file for legal protection through a civil lawsuit. A party who has suffered material losses as a result of a criminal act can file a civil lawsuit to recover the losses suffered in accordance with civil law. Civil lawsuits can be filed based on either breach of contract or an unlawful act.